An alternative algorithm for mapping stable parameters in Stock-Flow Consistent (SFC) models - Costa Santos, Júlio Fernando; Costa da Silva, Guilherme Jonas (Brazilian Keynesian Review, 2022)
This article describes the development of a stability analysis algorithm through a combination of Monte Carlo Simulation, Gauss-Seidel/Newton and Variation Filter techniques. In order to compare results, both the new algorithm and a numerical-analytical solution are tested against the Dos Santos and Zezza (2008) benchmark model. The outcome demonstrates overlap between the results from the two approaches. Considering that it is not always possible or feasible to analyze a system’s stability through an analytical solution, our algorithm innovates by providing an escape route for mapping stable parameters.